Republic of Latvia : Accounting and Auditing - World Bank (Washington, DC, 2012)
This report provides an assessment of accounting, financial reporting, and auditing requirements and practices within the enterprise and financial sectors in Latvia. The report uses International Financial Reporting Standards (IFRS) and International Standards on Auditing (ISA) as benchmarks and draws on international experience and good practices in the field of accounting and audit regulation. For European Union (EU) Member States, the assessment also has regard to the relevant requirements of EU law (also known as the acquis communautaire).